Dynamic Simulation on Energy Performance of a School. (November 2016) - Loreti, L.; Valdiserri, P.; Garai, M.
Abstract: Building retrofitting is the most feasible and cost-effective method to improve building energy efficiency. The paper presents a comparative analysis of two different strategies to enhance the energy performance of an existing building, trying to enhance indoor comfort conditions too. On one hand, the strategy aimed at reducing the heat transfer by transmission, on the other one at decreasing the heat transfer by ventilation. The study has been applied to a school, located in the surroundings of Bologna, Italy. Potential energy savings were calculated by dynamic simulation using Trnsys © software.